2015
DOI: 10.3389/fpls.2015.00339
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi and rhizobium facilitate nitrogen uptake and transfer in soybean/maize intercropping system

Abstract: The tripartite symbiosis between legumes, rhizobia and mycorrhizal fungi are generally considered to be beneficial for the nitrogen (N) uptake of legumes, but the facilitation of symbiosis in legume/non-legume intercropping systems is not clear. Therefore, the aims of the research are as follows: (1) to verify if the dual inoculation can facilitate the N uptake and N transfer in maize/soybean intercropping systems and (2) to calculate how much N will be transferred from soybean to maize. A pot experiment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(112 citation statements)
references
References 49 publications
6
94
0
5
Order By: Relevance
“…Proportion of fixed N 2 transferred from faba bean to wheat (Triticum aestivum L.) was 50% when inoculated with AMF compared 15% in uninoculated stands [52]. Similar results were also reported in garden pea-barley (Hordeum vulgare L.) and soybean-maize (Zea mays L.) intercropping studies [48,53]. The AMF-mediated transfer of N can be both unidirectional and bidirectional [48,54] and often along with a concentration gradient [47].…”
Section: Transfer Of Biologically Fixed Nitrogen In Agricultural Prodsupporting
confidence: 71%
“…Proportion of fixed N 2 transferred from faba bean to wheat (Triticum aestivum L.) was 50% when inoculated with AMF compared 15% in uninoculated stands [52]. Similar results were also reported in garden pea-barley (Hordeum vulgare L.) and soybean-maize (Zea mays L.) intercropping studies [48,53]. The AMF-mediated transfer of N can be both unidirectional and bidirectional [48,54] and often along with a concentration gradient [47].…”
Section: Transfer Of Biologically Fixed Nitrogen In Agricultural Prodsupporting
confidence: 71%
“…In the maize/soybean intercropping system, the yield advantage of maize has been also reported (Tang et al, 2005; Meng et al, 2015). In the present study, we demonstrated that the high competitive ability of maize relative to soybean can be partly ascribed to the contribution of AMF and rhizobia.…”
Section: Discussionmentioning
confidence: 86%
“…One common intercropping scheme is to pair a cereal crop with a legume that can supply N through biological N 2 fixation. Yield advantages of intercropping legumes with non-N 2 fixing crops have been found in many intercropping systems, including ryegrass-subclover (Ledgard et al, 1985), rice-peanut (Shen and Chu, 2004), wheat-faba bean (Xiao et al, 2004), Millet-cowpea (Laberge et al, 2011), rapeseed-faba bean (Jamont et al, 2013), and maize-soybean (Tang et al, 2005; Meng et al, 2015). Despite the prevalence of such cropping systems, the mechanisms underlying yield advantages of intercropping compared with monocropping systems have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A transferência de N entre as plantas leguminosas e não leguminosas pode ocorrer pela rizodeposição (exsudados radiculares) das raízes das leguminosas, por intermédio das micorrizas associadas às plantas leguminosas e não leguminosas, e liberação do gás amônia pelos adubos verdes (Hanstein, Mattsson, Jaeger, & Schjoerring, 1999;Lesuffleur, Salon, Jeudy, & Cliquet, 2013;Meng et al, 2015;Peoples, Chalk, Unkovich, & Boddey, 2015).…”
Section: Introductionunclassified